Crepna i vršnik. Mitološko – semiotička analiza Crepna and vrshnik. Mythological – Semiotic Analysis - Čausidis, Nikos; Nikolov, Gordan (Studia mythologica Slavica, 2006)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ansi-language: EN-US; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The paper focuses on the semiotic function of the crepna (bread baking dish) and the vrshnik (its cover). These traditional clay dishes were characteristic of the Balkans. Examined are several topics: the form of the crepna, which is reminiscent of the female body and therefore connected with a number of ritual magic procedures; female symbolism of the crepna; the crepna – dish – uterus – woman relation; and analogies and etymologies from Slavic languages. In popular tradition and phraseology, the crepna denotes earth while the vrshnik indicates the sky covering the earth. Examined is the custom in which a male effigy is placed on a peg wedged in the center of the crepna. The function of the male figurine was to protect the earthenware dish during the drying process. By employing semiotic and comparative analyses, and in relation with the mythological German, the author investigates the role of German and his implicit function as fecundator, mediator, and god sacrificed on the cosmic axis. The paper then looks at medieval Slavic, Indo-European, and worldwide parallels in art. One of the symbolic postulates is the analogy between the making of bread (kneading, leavening, baking) and the growth of a baby inside its mother’s womb. In this respect, the crepna dish attains the character of the uterus – the mother of the bread and earth. The yeast represents the father of the bread, and the sperm means the rain.